Efektivitas Penggunaan Media Finger Painting Terhadap Kemampuan Menulis Permulaan Anak Usia Dini 5-6 Tahun di Tkq An-Namlu Karawang - Vicky Widyananda; Astuti Darmiyanti; Feronica Eka Putri (Peneliti.net, 2022)
The purpose of this study was to determine the effect of finger painting media on children's writing skills. This study used an experimental methodology with a sample of 10 children aged 5-6 years from group B, using a one-group pre-test-post-test design. The survey was conducted 10 times in class B TKQ An-Namlu Karawang. According to survey findings and data analysis, early childhood writing skills improved by 34 and 57 points on pretest and posttest, respectively. The findings of the Paired Sample T-Test table show the t-count value of 36,037 and sig (0.000). Therefore, it can be said that finger painting media has a significant influence on children aged 5-6 years.